2017
DOI: 10.1002/iub.1681
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SOX2‐OT is a novel prognostic biomarker for osteosarcoma patients and regulates osteosarcoma cells proliferation and motility through modulating SOX2

Abstract: Long noncoding RNA (LncRNA) SOX2 overlapping transcript (SOX2-OT) has been shown to serve an oncogenic role in human lung cancer, hepatocellular carcinoma, and gastric cancer. However, the clinical significance and biological function of lncRNA SOX2-OT in osteosarcoma are still unclear. LncRNA SOX2-OT expression was measured in osteosarcoma tissues and cell lines. Loss-of-function and gain-of-function studies were performed to observe the effects of lncRNA SOX2-OT on osteosarcoma cells proliferation, migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
(37 reference statements)
2
51
0
Order By: Relevance
“…Stepwise mechanistic studies revealed ARAP1-AS1 enhanced c-Myc translation through competitively binding to PSF and dissociating PSF/ PTB complex, thereby promoting CC progression (Figure A growing body of evidence suggests that lncRNA is an effective biomarker of cancer. 16 For instance, LncRNA SOX2-OT, 17 EGFR-AS1, 18 LOC101928316, 19 and ZFAS1 20 were, respectively, identified as diagnostic or prognostic biomarkers for osteosarcoma, squamous cell carcinoma, gastric cancer, and colorectal cancer. In this study, we found that CC patients with high ARAP1-AS1 expression had shorter survival than patients with low ARAP1-AS1 expression, implying that ARAP1-AS1 is a promising prognostic biomarker for CC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Stepwise mechanistic studies revealed ARAP1-AS1 enhanced c-Myc translation through competitively binding to PSF and dissociating PSF/ PTB complex, thereby promoting CC progression (Figure A growing body of evidence suggests that lncRNA is an effective biomarker of cancer. 16 For instance, LncRNA SOX2-OT, 17 EGFR-AS1, 18 LOC101928316, 19 and ZFAS1 20 were, respectively, identified as diagnostic or prognostic biomarkers for osteosarcoma, squamous cell carcinoma, gastric cancer, and colorectal cancer. In this study, we found that CC patients with high ARAP1-AS1 expression had shorter survival than patients with low ARAP1-AS1 expression, implying that ARAP1-AS1 is a promising prognostic biomarker for CC patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 SOX2-OT has been reported to be upregulated in laryngeal squamous cell carcinoma and regulate osteosarcoma cells proliferation and motility through modulating SOX2. 9,25 Nevertheless, the biological significance and regulatory mechanism of SOX2-OT in NPC progression are largely to be clarified. In the present study, we found the expression level of SOX2-OT was higher in NPC tissues than that in the matched nonneoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs exhibit tissue specificity and functional diversity, which makes them potentially effective diagnostic and prognostic markers (8). Recent studies have revealed that lncRNA SOX2-OT functions as an oncogenic factor and serves an important role in numerous types of cancer, including osteosarcoma, cholangiocarcinoma and lung squamous cell carcinoma (9)(10)(11). Notably, using microarrays, Feng et al (12) identified that the expression of SOX2-OT in cancer tissues was significantly higher compared with that in adjacent non-neoplastic tissues in advanced laryngeal squamous cell carcinoma (LSCC).…”
Section: Introductionmentioning
confidence: 99%